2013
DOI: 10.1118/1.4792295
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of four‐dimensional hybrid depth scanning for carbon‐ion lung therapy

Abstract: PCRL requires a longer treatment time than PCRV for high numbers of rescannings in the NIRS scanning system but is more robust. Although four or more rescans provided good dose homogeneity and conformity, the authors prefer to use more rescannings for clinical cases to further minimize dose degradation effects due to organ motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…Such a solution is not yet feasible due to the complexity of the problem. Another solution could also be phase-controlled rescanning with greatly reduced uncertainty in the mitigation outcome [Mori et al, 2013, Takahashi et al, 2014. However, it requires motion monitoring and complicates the treatment delivery.…”
Section: Treating Non-small Cell Lung Cancer With Particle Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Such a solution is not yet feasible due to the complexity of the problem. Another solution could also be phase-controlled rescanning with greatly reduced uncertainty in the mitigation outcome [Mori et al, 2013, Takahashi et al, 2014. However, it requires motion monitoring and complicates the treatment delivery.…”
Section: Treating Non-small Cell Lung Cancer With Particle Therapymentioning
confidence: 99%
“…Recent studies suggest that some patients require phase-controlled layer or volumetric rescanning for sufficiently robust target coverage [Mori et al, 2013, Takahashi et al, 2014. The advantage of simple slice-by-slice rescanning is that no motion monitoring or assumptions on the breathing frequency are necessary [Bert and Durante, 2011], but the higher required number of rescans might increase treatment times due to reduced beam intensities.…”
Section: Range Margins and Motion Mitigationmentioning
confidence: 99%
“…In 2011, clinical trials were completed at NIRS using the PBS method, demonstrating improved dose distribution and reinforcing the results of international centers (4,5). Initial usage was limited to static sites, as development to compensate for respiratory motion and consequential interplay effects continued (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…We do this on the basis of our previous studies, which showed that four or more phase-controlled rescans with FTV should substantially improve the accuracy of dose delivery, and it is indeed close to that calculated by our present approach. [20][21][22] In the present study, we introduced an alternative approach to four dimensions. This approach does not calculate 4D accumulated dose distribution using DIR, for the following reason.…”
Section: Discussionmentioning
confidence: 99%